Promoting healthy aging in a digital world: leveraging technology for enhanced elderly care and wellbeing - Armeni, Patrizio; Polat, Irem; De Rossi, Leonardo Maria; Diaferia, Lorenzo; De Padova, Sara; Gatti, Athena; Meregalli, Severino (Frontiers in Aging, 2026)
The rising demands of an aging population underscore the need for digital health technologies (DHTs) in elderly care. Traditional services, which rely heavily on face-to-face, human-dependent interactions by medical and nursing staff, may struggle to meet these needs amid growing healthcare workforce shortages. This review examines the emerging role of DHTs—including wearable sensors, artificial intelligence (AI), robotics, and virtual reality (VR)—in supporting healthy aging. These technologies offer promising solutions to challenges such as chronic disease management, mobility impairments, cognitive decline, and social isolation. However, despite their potential, their adoption and integration into care systems remain limited due to a range of barriers. While we identify these barriers in detail, we also aim to open a broader discussion on why the urgency to act is particularly pronounced in Europe. The continent faces a sharp demographic shift, combined with uneven digital readiness across countries, under-resourced long-term care systems, and regional disparities in access to innovation. To fully harness the potential of DHTs in promoting healthy aging, this review outlines six strategic priorities: improving user-centered design; expanding real-world validation; promoting digital inclusion; addressing ethical and regulatory concerns; defining appropriate reimbursement and funding pathways; and innovating care delivery models. Advancing these areas will be critical to ensuring that DHTs contribute meaningfully to equitable and sustainable aging.